Educational intervention based on health action model to promote safe behavior of hospital service workers - Maryam Mohammadi; Mohammad Vahedian-sharoodi; Zahra Joghatei; Habibullah Esmaily; Hadi Tehrani (BMC, 2023)
Abstract Background Hospitals are considered to be one of the most hazardous environments to work in, and their service workers are exposed to many serious risks. So The purpose of this study was to investigate the effect of educational intervention based on the Health Action Model to promote the safe behavior of hospital service workers. Methods In this quasi-experimental study, 45 workers in each of the control and experimental groups participated. Demographic information and data related to Health Action Model constructs were collected through a questionnaire and a checklist, immediately and three months after the intervention. Cronbach's alpha coefficients were used to confirm the properties of the tools. Educational intervention accompanied was applied in the form of four training classes. The data were analyzed using SPSS 20 software. Results Before the intervention, there was no significant difference between the two groups in terms of demographics and the study's main variables. results showed significant changes in mean scores of safe behavior, Attitude, norms, belief, intention, knowledge in the experimental group three months after the intervention (P < 0.001). Conclusions The research results show that Health Action Model educational intervention can change workers' awareness, attitudes, norms, beliefs, and intentions toward unsafe behavior and improve their safety performance. Trial registration IRCTID: IRCT20160619028529N7.